The Strength of American Federal Democracy : Lessons for Global Development - Myerson, Roger B. (World Bank, Washington, DC, 2015)
A review of the history of the United States from its colonial origins shows how Americas successful development has always been guided by two basic principles: representative democracy, and a proper division of power between national and subnational governments. The United States of America was established as an independent nation by a congress of delegates from 13 provincial assemblies, each of which consisted of representatives elected by their communities. Since colonial times, local democratic rights have attracted immigrants to help build new towns in the growing nation. Responsible local governments in America have had the power and the incentive to make local public investments for developing prosperous communities. Democratic competition in America has been strengthened by the ability of successful local leaders to become competitive candidates for higher offices. But in spite of Americas example, many nations since the French Revolution have instead been drawn to centralized democracy, as national elites may prefer to centralize power around themselves. Americas successful growth ultimately depended on its citizens basic understanding that their welfare and security were enhanced by a balanced federal division of power between their elected local governments and the higher sovereign government of their nation.